Donor prone positioning protects lungs from injury during warm ischemia. Issue 10 (25th April 2019) - Watanabe, Yui; Galasso, Marcos; Watanabe, Tatsuaki; Ali, Aadil; Qaqish, Robert; Nakajima, Daisuke; Taniguchi, Yohei; Pipkin, Mauricio; Caldarone, Lindsay; Chen, Manyin; Kanou, Takashi; Summers, Cara; et al.
Abstract : A large proportion of controlled donation after circulatory death (cDCD) donor lungs are declined because cardiac arrest does not occur within a suitable time after the withdrawal of life‐sustaining therapy. Improved strategies to preserve lungs after asystole may allow the recovery team to arrive after death actually occurs and enable the recovery of lungs from more cDCD donors. The aim of this study was to determine the effect of donor positioning on the quality of lung preservation after cardiac arrest in a cDCD model. Cardiac arrest was induced by withdrawal of ventilation under anesthesia in pigs. After asystole, animals were divided into 2 groups based on body positioning (supine or prone). All animals were subjected to 3 hours of warm ischemia. After the observation period, donor lungs were explanted and preserved at 4°C for 6 hours, followed by 6 hours of physiologic and biological lung assessment under normothermic ex vivo lung perfusion. Donor lungs from the prone group displayed significantly greater quality as reflected by better function during ex vivo lung perfusion, less edema formation, less cell death, and decreased inflammation compared with the supine group. A simple maneuver of donor prone positioning after cardiac arrest significantly improves lung graft preservation and function. Abstract : This study demonstrates the efficacy of donor prone positioning in preventing lung injury during periods of warm ischemia in a donation after cardiac death.